Health workers' experience of providing second-trimester abortion care in Ethiopia: a qualitative study - Emily McLean; Astrid Blystad; Alemnesh H. Mirkuzie; Ingrid Miljeteig (BMC, 2023)
Abstract Background Second-trimester abortions are less common than abortions in the first trimester, yet they disproportionately account for a higher burden of abortion-related mortality and morbidity worldwide. Health workers play a crucial role in granting or denying access to these services, yet little is known about their experiences. Ethiopia has been successful in reducing mortality due to unsafe abortion over the past decade, but access to second trimester abortion remains a challenge. The aim of this study is to better understand this issue by exploring the experiences of second-trimester abortion providers working in Addis Ababa, Ethiopia. Methods A qualitative study with 13 in-depth semi-structured interviews with 16 health workers directly involved in providing second-trimester abortions, this included obstetrician and gynaecologist specialists and residents, general practitioners, nurses, and midwives. Data was collected at four public hospitals and one non-governmental clinic in Addis Ababa, Ethiopia and analysed using Malterud's text-condensation method. Results The providers recognized the critical need for second-trimester abortion services and were motivated by their empathy towards women who often sought care late due to marginalisation and poverty making it difficult to access abortion before the second trimester. However, service provision was challenging according to the providers, and barriers like lack of access to essential drugs and equipment, few providers willing to conduct abortions late in pregnancy and unclear guidelines were commonly experienced. This led to highly demanding working conditions. The providers experienced ethical dilemmas pertaining to the possible viability of the fetus and women desperately requesting the service after the legal limit. Conclusions Second-trimester abortion providers faced severe barriers and ethical dilemmas pushing their moral threshold and medical risk-taking in efforts to deliver second-trimester abortions to vulnerable women in need of the service. Effort is needed to minimize health system barriers and improve guidelines and support for second-trimester abortion providers in order to increase access and quality of second-trimester abortion services in Ethiopia. The barriers forcing women into second trimester abortions also need to be addressed.